2020
DOI: 10.3390/rel11090451
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Spiritual and Existential Care Needs in Health Education: Applying SOPHIE (Self-Exploration through Ontological, Phenomenological, and Humanistic, Ideological, and Existential Expressions), as Practice Methodology

Abstract: Addressing existential and spiritual care needs, often remains a challenge in health education. Spirituality is a subjective human experience that shapes how individuals make meaning, construct knowledge, develop their own sense of reality, and bring personal and social transformation. To inspire health and social students at a London based University; learners were engaged into philosophical reasonings associated with the meaning to care. SOPHIE (Self-exploration through Ontological, Phenomenological and Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The themes of life and death, absurdity and meaning, as addressed by Camus, have increased in importance during the Covid-19 pandemic. Researchers highlight that a new focus on these topics has been created by individuals, societies and humankind finding themselves being threatened by the experience of an existential crisis during the pandemic (Ali and Lalani, 2020 ), being preoccupied with questions of death—as in Camus' La Peste (1947). Vulliamy ( 2015 ) explains that during pandemics, humankind focuses on death and becomes preoccupied with it, confronts it on an epic scale, while continuing to fight it under consideration of “ill-defined moral justice.” Ingram ( 2016 ) points out that through the constant threat of the pandemic, morality is equally threatened and confusion arises with regard to how to understand the new situation, how to deal with it and how to define meaning in the occurrence of the new threat.…”
Section: The Meaning Of Camus In Times Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The themes of life and death, absurdity and meaning, as addressed by Camus, have increased in importance during the Covid-19 pandemic. Researchers highlight that a new focus on these topics has been created by individuals, societies and humankind finding themselves being threatened by the experience of an existential crisis during the pandemic (Ali and Lalani, 2020 ), being preoccupied with questions of death—as in Camus' La Peste (1947). Vulliamy ( 2015 ) explains that during pandemics, humankind focuses on death and becomes preoccupied with it, confronts it on an epic scale, while continuing to fight it under consideration of “ill-defined moral justice.” Ingram ( 2016 ) points out that through the constant threat of the pandemic, morality is equally threatened and confusion arises with regard to how to understand the new situation, how to deal with it and how to define meaning in the occurrence of the new threat.…”
Section: The Meaning Of Camus In Times Of Covid-19mentioning
confidence: 99%
“…Schnell and Krampe ( 2020 ) confirm that meaning-in-life questions have increased during the pandemic—particularly through prosocial acts and creative expressions. The creation of meaning in life can be viewed as a psychological resource, and people with high levels of meaningfulness are viewed as more hopeful, optimistic, and stress-resistant, while people with low levels of meaning are usually threatened by loss of identity, suicide, higher levels of pain and suffering and aggravated distress during the pandemic (Ali and Lalani, 2020 ). The authors have found that people with high levels of meaning during the pandemic are far more resilient and successfully cope with life's challenges during this time.…”
Section: The Meaning Of Camus In Times Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Spiritual awareness and reflexivity are considered critical in the provision of spiritual care. 24 Different theoretical frameworks and models of spirituality signify the importance of holistic and humanistic approaches to care and guide nursing to improve the overall well-being and quality of life of patients and families in practice settings.…”
Section: Theories/models Of Spiritualitymentioning
confidence: 99%
“…The tool "SOPHIE" is based on the principles of intentionality, reflexivity, and creativity and allows several strategies to integrate application of spiritual assessments and models in clinical practice settings. 24 Innovative educational strategies such as simulations and reflective practice tools have been found to be effective approaches to teach nursing students about how to assess spirituality and perform spiritual care in clinical settings. 23,28,29 Specific communication trainings and workshops should be designed to help nurses feel comfortable while assessing spiritual needs and concerns of their patients and families.…”
Section: Way Forward: Tools To Integrate Spirituality In Nursing and ...mentioning
confidence: 99%